2010
DOI: 10.3109/03009730903457218
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dysmenorrhea and its effect on quality of life among a group of female university students

Abstract: The objective was to evaluate the prevalence of dysmenorrhea and determine its effect on health-related quality of life (HRQoL) among a group of female university students. This cross-sectional study was conducted between 15 March and 15 April 2009 at Dumlupinar University, Kutahya, Health High School, Western Turkey. The study group included 623 female students. The severity of dysmenorrhea was determined with a 10-point visual analog scale. The Short Form-36 (SF-36) form was used to determinate HRQoL. Chi-sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

52
279
10
35

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 343 publications
(376 citation statements)
references
References 23 publications
52
279
10
35
Order By: Relevance
“…kadın üniversite öğrencilerinde dismenore prevelansını araştırdıkla-rı bir çalışmada 623 kadın öğrenciyi sorgulamışlar ve % 72.7'sinin dismenoresi olduğunu bildirmişler-dir. Aynı çalışmada dismenoreli bireylerin menarş yaşı ortalamalarını 13.38 yıl olduğunu ve menarş yaşının dismenoresi olan ve olmayan bireylerde değişiklik göstermediğini bulunmuştur (40). Çalışma-mızda yer alan 100 olgunun menarş yaşı ortalaması 13.45±1.35 olarak tespit edilmiştir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…kadın üniversite öğrencilerinde dismenore prevelansını araştırdıkla-rı bir çalışmada 623 kadın öğrenciyi sorgulamışlar ve % 72.7'sinin dismenoresi olduğunu bildirmişler-dir. Aynı çalışmada dismenoreli bireylerin menarş yaşı ortalamalarını 13.38 yıl olduğunu ve menarş yaşının dismenoresi olan ve olmayan bireylerde değişiklik göstermediğini bulunmuştur (40). Çalışma-mızda yer alan 100 olgunun menarş yaşı ortalaması 13.45±1.35 olarak tespit edilmiştir.…”
Section: Discussionunclassified
“…Dismenoreli ve normal menstruasyon geçiren kadınların menarş yaşı ortalamaları ve siklus düzenleri arasında istatistiksel olarak anlamlı bir fark bulunmamıştır. Bu bulgu menarş yaşının toplumumuzda dismenoreyi etkileyen bir faktör olmadığını göstermektedir ve önceki çalışmalar ile uyumlu bir bulgudur (12,40).…”
Section: Discussionunclassified
“…Emotional and behavioral problems like anxiety, s t r e s s , a n d d e p r e s s i o n m a y e x a c e r b a t e dysmenorrhea. 3,11 Though dysmenorrhea is a common gynecological problem, enough hospital-based studies have not been done in Nepal to know the true extent of this problem. The aim of this study is to describe the presenting complaints in the Gynecological OPD in a tertiary hospital of Kathmandu and to describe the prevalence and assess the extent of dysmenorrhea and its impact on daily activities in the women visiting the OPD.…”
Section: Introductionmentioning
confidence: 99%
“…2 Primary dysmenorrhea is painful menstruation without any underlying pathology while secondary dysmenorrhea is the one associated with underlying pathology. 3,4 Dysmenorrhea is commonest problem of menstruation affecting adolescent age females with prevalence ranging from 40-91%. 3,5 A study in Virginia, USA showed that primary dysmenorrhea was present in 40-50% of menstruating females and caused significant disruption in quality of life and absenteeism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation